The significance of osteosarcopenia as a predictor of the long‐term outcomes in hepatocellular carcinoma after hepatic resection. (19th October 2022) - Yanagaki, Mitsuru; Haruki, Koichiro; Taniai, Tomohiko; Igarashi, Yosuke; Yasuda, Jungo; Furukawa, Kenei; Onda, Shinji; Shirai, Yoshihiro; Tsunematsu, Masashi; Ikegami, Toru
Abstract: Background: Frailty, represented by sarcopenia and osteopenia, has been associated with worse survival after hepatectomy in patients with hepatocellular carcinoma. Recently, the concept and term "osteosarcopenia" have been proposed, which has been associated with worse outcome in several malignancies. Methods: This study included 227 patients who underwent elective hepatic resection for hepatocellular carcinoma. Osteopenia was evaluated with computed tomographic measurement of pixel density in the midvertebral core of the 11th thoracic vertebra. The skeletal muscle index (SMI) was evaluated with psoas muscle areas at the third lumbar vertebra. Osteosarcopenia was defined as the concomitant occurrence of osteopenia and low SMI. We retrospectively investigated the relationship between osteosarcopenia and disease‐free and overall survival. Results: Osteosarcopenia was identified in 27 (12%) of the patients. Multivariate analysis showed that osteosarcopenia ( P < .001), C‐reactive protein‐to‐albumin ratio ≥0.02 ( P = .002), and stage ≥III ( P ≤ .001) were independent predictors of disease‐free survival, while osteosarcopenia ( P < .001), Child‐Pugh grade B ( P = .002), C‐reactive protein‐to‐albumin ratio ≥0.02 ( P = .001), low SMI ( P ≤ .001), and stage ≥III ( P ≤ .001) were independent predictors of overall survival. Conclusion: Preoperative osteosarcopenia may be a prognostic factor in patients with hepatocellular carcinoma after hepatic resection. Our results suggests that the preoperative maintenance of skeletal muscle and bone density may potentially improve prognosis. Abstract : Yanagaki and colleagues found that preoperative osteosarcopenia, which is the concomitant occurrence of sarcopenia and osteopenia, can be a useful prognostic indicator in patients who have undergone hepatic resection for hepatocellular carcinoma. Their findings suggest that the preoperative maintenance of skeletal muscle and bone density may potentially improve prognosis.